Teaching basic concepts of cryptography in professional high school - Marin, Regina Paiva Melo; Souza , Jackson Gomes Soares; Marin, Luciano Heitor Gallegos (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The cryptography is present in several operations performed daily by people, such as online shopping or in dialogues using computer equipment and the Internet as a proxy. Although cryptography is very important in the contemporary context, the teaching of the cryptography subject is new for students at professional high school. In this regard, one of the biggest challenges is to motivate students in using the cryptographic methods in the classroom. The objective of this work is to investigate the use and learning of cryptography by students at professional high school. For this purpose, the Survey methodology was used with self-evaluative questions about the motivation, understanding and the use of computational tools containing basic cryptography concepts. An analysis of the responses suggests that most students find the cryptography subject difficult to learn, but all of them were able to practice and learn at least one of the cryptographic techniques taught.